Evaluation and improvement of accessibility to urban Rail Transit System in Klang Valley, Malaysia / Suhana Koting - Suhana, Koting (2017)
In Urban Rail Development Plan 2013 and Kuala Lumpur Structure Plan 2020, issue on poor accessibility to rail-based public transport has been highlighted and become the focus in urban transportation planning in Klang Valley, Malaysia. This research aims to evaluate and improve the accessibility from home to urban rail transit system in Klang Valley. The primary data was obtained from N=569 individuals. The sample size for frequent rail users was, N = 335 individuals and for private transport users was N = 234 individuals. The research objective is to investigate the influence of access and travel characteristics scenarios as well as socio-demographic factors on the willingness of frequent rail users/private transport users to travel consistently by rail/private transport and the potential of shifting to private transport/rail transit. The Binomial Logistic Models (BNL) were developed for each travel mode choice preference, namely (1) rail transit and (2) private transport mode with respect to different hypothetical stated preference scenarios. The results revealed that frequent rail users were fairly influenced by access time and access distance increment rather than access cost increment. In addition, frequent rail users were more affected by travel time increment rather than travel cost increment. In addition, the objective of this study is to identify and investigate the current access modes indicators that are priorities for enhancement based on the users’ satisfaction and importance level. The Importance-Performance Analysis (IPA) was applied to assess the importance and satisfaction level of rail access indicators offered by different access modes utilities. The findings implied that major improvement works on the disabled persons facilities, safety in the station, walking comfort and access time have to be implemented on current access mode utilities to provide more pleasant travel experiences and simultaneously induce modal shift to rail transit. The suggestion to improve the walking surface for pedestrian accessing the rail transit station was also focused. Through laboratory investigation, the semi-flexible pavement surfacing was found to be an appropriate alternative as a walkway surfacing material. An evaluation on (i) the rail transit system traits that is of importance and priority to frequent rail users and (ii) the development of structural model for perceived importance of rail transit system through Structural Equation Modelling (SEM) approach are also focused in this study. Based on analysis, the service realibility and safety were discovered as the attributes that should be prioritized in the rail transit system improvement. It was discovered that perceived service quality of rail transit system and rail users travel experience exhibited significant contribution towards the perceived importance of rail transit system traits. Conclusively, in order to ensure frequent users to consistently travel with rail and to encourage occasional rail users and auto-dependent travellers to use rail, improvements on existing rail access and efficient rail transit services is needed. Furthermore, the findings from this study can be contributed in implementing the well-grounded transport policies for both public and private transportation to attain ideal modal shift in Klang Valley and become more liveable urban area in Malaysia